Effectiveness of adapted cognitive behaviour therapy for dysthymia: an evidence based case study - Sameera Shafiq; Zaqia Bano; Shahid Sharif Randhawa; Khalid Hayat Khan; Qurat-ul-Ain Muhammad; Abdullah Muhammad (Journal of the Pakistan Medical Association, 2022)
Several empirical researches imply that cognitive behaviour therapy can be effective in treating psychiatric disorders. In the context of Pakistan, some researches with Culturally Adapted Cognitive Behaviour Therapy were found to be effective for depression, anxiety, bipolar and psychotic disorders. The present study theoretically underpinned the model of Adapted Cognitive Behaviour Therapy (ACBT) based on the inclusion of Tasbeehs (Rosary) derived from the Quran and Sunnah to be fruitful in producing the desirable change in a single case of Dysthymia with anxious distress which was assessed with the help of the Urdu versions of Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI), Beck Hopelessness Scale (BHS) and Beck Scale for Suicidal Ideation (BSS). ACBT produced profound differences in pre-test and post-test scores in a patient. The Tasbeeh or Rosary could provide a therapeutic means for treating psychiatric illnesses irrespective of the religious and cultural differences. Continue..